Relationship Between Execution of Quality Management Practices and Firm’s Innovation Performance: A Review of Literature (Journal of Asian Development Studies, 2023)
This research study was conducted with the main objective of reviewing the impactful published research and exploring the nature of the association between the execution of total quality management (TQM) and a firm’s innovation performance (IP) relation. Despite the strategic significance of both TQM and innovation for organizational sustained competitive gain, this is an under-researched area and a debatable issue among academia. For this purpose, a systematic literature review (SLR) was conducted covering the period 2003 to 2023 based on impact factor journals from databases (Scopus, WOS, cross-ref, Google Scholar, Etc.). SLR was applied to identify published research and analyze these papers to find out emerging research trends and potential gaps in the field for future research. In the final selection, 110 papers were shortlisted and analyzed to present findings and directions for future research. The earlier studies and the literature reveal inconclusive findings regarding this association. Few scholars report negative or no association between these two constructs. At the same time, many studies support the positive impact between the execution of TQM and the firm’s Innovation (FI). Based upon LR, this paper identifies key practices and dimensions of QM that are more impactful for a firm’s innovation (FI) and innovation performance (IP). Findings indicate that literature recognizes soft and hard QM dimensions or practices in relevance to a firm’s innovation and IP.